Adaptasi Teknologi Pembibitan Kentang untuk Menunjang Pengembangan Kawasan Agribisnis di Kecamatan Pasirwangi, Kabupaten Garut Program Pengabdian Masyarakat Dengan Skim Ipteks Bagi Masyarakat (IbM) - Ibrahim Danuwikarsa; Okke Rosmaladewi; Rubi Robana (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2011)
Community Service Program with scheme of the science and technology for Community (IbM) in the form of seed potato technology adaptation has been implemented in Padaawas village since May 2010 until December 2010 to support agribusiness in Pasirwangi district, Garut regency. The technology  of potato breeding adaptation chosen because during this time the needs of seed are supplied from outside area whose quality of the seed is not necessarily satisfactory. The purpose of this program is to introduce and practice potato breeding, particularly how to produce G4 seeds (Spreading Seeds) from G3 seed (Primary Seed) and form The Joint Business Group (KUBE) as a medium for carrying out agribusiness, especially in the procurement, distribution and marketing of G4 seed potatoes. This program succeeded training and practicing the technology of potato breeding adaptation to the representative participants from 12 villages at the level of Pasirwangi districts. Obtaining good potatoes vigorite, although in the early stages it was interrupted by high rainfall and humidity. The program would be continued on growing season in 2011, for demonstration plots repetition of the technology potato breeding adaptation in different locations and seasons as well as improving The Joint Business Group (KUBE) economic institutions.